Consumer Behavior in Online Transportation Services: A Systematic review of Business Strategies - Jafar Basalamah; Muh. Haerdiansyah Syahnur; Muhammad Ashoer; Andi Faisal Bahari (Yayasan Ilomata, 2020)
Purpose: The reasons for the paper are: first, recognize the components of the online transportation Services with shopper conduct (utilizing, reusing, item returns); second, comprehend the connection between Services acknowledgment and purchaser conduct; third, for Research and improvement of client support system that considers this social reaction to arrange execution results. Design/methodology/approach: This paper depends on a precise survey of customer conduct and Services execution (particularly in the field of online transportation), which distributed in the International Journal from 2005 to 2017. Findings: The article shows that present writing on purchaser conduct centers around the utilizing of instruments for advertising to improve client support. There are not many examinations on the utilization of purchaser Services instruments to direct buyer conduct or to deal with the execution of corporate Services. The outcome is a system that incorporates the components of transportation Services and the relationship to shopper conduct. Originality/value: This article is a thorough audit of shopper conduct, thinking about all parts of Services execution from the point of view of business technique.